Impact of Liquidity Shortage Risk on Financial Performance of Sudanese Islamic Banks - Mustafa, Omer Allagabo Omer (International Journal of Islamic Economics and Finance (IJIEF), 2020)
The paper aims to examine the impact of Liquidity Shortage Risk (LSR) on the financial performance of Islamic Commercial Banks (ICBs) in Sudan (1992-2018). The following explanatory powers were used to indicate LSR; which include: liquid assets to total assets, total finance to total deposits, current deposits to total deposits and inflation as a control factor. The financial performance of ICBs (the dependent variable) was measured by the Return on assets. To concludes the relation between the variables, data were analyzed thought used Ordinary Least Squares technique. The main findings revealed that current deposits to total deposits, total finance to total deposits and inflation negatively affected the financial performance. While liquid assets to total assets have positive influence to the performance of ICBs. Monetary policy indirectly contributed to the exposure of ICBs to LSR through money supply increase. Moreover, high inflation motivated depositors to high cash withdrawal from their deposits; and, consequently exposed ICBs to LSR. The study recommends that ICBs should not wholly depend on current deposits as a source of finance, because customersÊ¹ default might lead to LSR resulting in deteriorating profitability. Moreover, diversification of financial assets (with high liquidity) protects them from LSR. Â As for the central bank, the contractionary monetary policy is a crucial to control inflation in order to improve the financial performance of ICBs.